Development of microcomputer-based laboratory (MBL) apparatus in tertiary physics education - Hussain Baseri Huddin, Jaafar Rosly, Wan Mokhtar Wan Zul Adli, Yaacob Mohd Ikhwan Hadi, Hanif Abd Samad, Othman Md Zahar (Universiti Pendidikan Sultan Idris, 2010)
Development of microcomputer-based laboratory (MBL) apparatus in tertiary physics education by Hussain Baseri Huddin, Jaafar Rosly, Wan Mokhtar Wan Zul Adli, Yaacob Mohd Ikhwan Hadi, Hanif Abd Samad, Othman Md Zahar,